Evaluation Framework For Core Banking Modules Based On Business Intelligence Criteria - Saeed Rouhani; Homa Hamidi (Journal of Information Technology Management)
This research attempted to evaluate Business Intelligence criteria accelerating further development of Core Banking System with creating meaningful analysis, decision support environment and optimizing the investments. By reviewing the related literature, Business Intelligence criteria were determined and the importance and priority of each criterion specified on the basis of questionnaire and doing Friedman and Binomial tests. This research presented an evaluation model based on the fuzzy multi-criteria decision making (Fuzzy TOPSIS) method. In the fuzzy-based method, weight of each criterion and results of assignable intelligence were described using linguistic terms, which can also be expressed as triangular fuzzy numbers. According to the findings, Risk Management System ranked as the first module with the largest distance from the negative ideal which indicated that this system had appropriate Business Intelligence capabilities to fortify decision support environment.